Kekayaan Intelektual Sebagai Objek Jaminan Fidusia: Perspektif Keabsahan Hukum dan Mekanisme Penilaian - Nilandari, Ni Wayan; Samsithawrati, Putu Aras (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 02 (2023), 2023)
This study aims to examine and elaborate more comprehensively regarding the legal validity of intellectual property as an object of fiduciary guarantees in obtaining bank credit facilities for creative economy actors and to elaborate on the mechanism for intellectual property valuation and the approach used in determining the economic value of intellectual property. This study used a type of normative legal research method with a statutory approach and legal concept analysis. The results of the study indicated that the validity of intellectual property as a fiduciary guarantee is contained in various provisions, namely Law 28/2014, Law 13/2016, Creative Economy Law and PP 24/2022. The category of intellectual property that can be used as a fiduciary guarantee is normatively determined to be only intellectual property that has been registered and registered at the ministry responsible for legal affairs and intellectual property, namely registered and registered with the Directorate General of Intellectual Property, as well as intellectual property that has been managed either independently or by transferring rights to other parties. PP 24/2022 has explicitly regulated the mechanism for bank and non-bank financial institutions in providing access to intellectual property-based financing for creative economy actors, namely by evaluating the intellectual property that is used as collateral, using several approaches, namely: the cost approach, the market approach, the income approach and/or other valuation approaches in accordance with the applicable valuation standards.